Pendidikan Akhlak (Komparasi Pemikiran Ibnu Miskawaih dan AL-Gazālī) - Krisnando, Andika Ukik; , Drs. Suharjianto, M.Ag (2016)
Moral education in general are distinguished into two categories, namely moral education rational and moral education of sufism. One of the classic philosophers considered mazhab rational moral education is Ibnu Miskawaih. Whereas considered a classic figure mazhab sufism moral education is Al-Gazālī. Ibnu Miskawaih and Al-Gazālī was a prominent Muslim representative in the field of morals (ethics), moral education thought both figures can be revived into modern times, in order to filter the currents of globalization and knowledge of information technology that is constantly evolving. So the creation of a critical human, intelligent, and noble moral in the middle of the rate of development of the times. Based on the background of the problems mentioned above, the purpose of this research is to know how the thought of Ibnu Miskawaih and Al-Gazālī about moral education, and to find out how the similarities and differences of thinking between Ibn Miskawaih with Al-Gazālī about moral education. This type of research is a library research with the philosophical approach. From the research that has been done, the author finds that: (1) Education moral thought Ibnu Miskawaih that is human essence lies in the faculty think (through the brain), and the concept of the middle way doctrine, namely their ways as the basis of moral virtue, where the size is reasonable and the religion. The purpose of education their ways are social. Educational material covering their ways; the science of jurisprudence, the science of morals, and morals. A method of education that is natural, conditioning their ways, riyāḍah and mujāhadah. The obligation to educate first-time is his parents. Education moral thought of Al-Gazālī that is the very essence of man lies in the strength of knowledge (through the liver), and the concept of the middle way doctrine, namely their ways as the basis of moral virtue, where the size is reasonable and the religion. Their ways are individual educational objectives. Educational material according to the morals of all their ways commendable jurisprudence. Method of education their ways through a gift from God and perfection of fiṭri, conditioning, riyāḍah and mujāhadah. According to him, the parents are the first educators for a child. Then, the environment and food or beverage item will affect the the formation of a moral person. (2) The overall moral education thought of Ibnu Miskawaih and Al-Gazālī has a lot in common. Key Words: Moral Education, Ibnu Miskawaih, Al-Gazālī